Histomorphological changes in the Heart of Sheep (Ovies Aries) during early gestation - Veeresh, PG; lakshmi, M Santhi; Ramayya, P Jagapathi; Bharathi, S (Indian Journal of Veterinary Anatomy, 2023)
The study was conducted on 10 hearts of prenatal sheep (embryos and fetuses) ranging from 22 days to 50 days. Histologically, cardiac loop, endocardial cushions, spiral septum were noticed at 22 days. Septum primum and septum secundum were noticed at 24 and 36 days respectively. The primitive heart showed four chambers with incomplete septation in the atrium at 31 days. Foramen ovale was observed at 36 days, three distinct layers in the wall of atria and ventricles were observed at38 days andPurkinje fibers were seen at47 to 50 days.